SANMAI NO OFUDA DALAM PERSPEKTIF GREIMAS - Yuliani Rahmah (IZUMI, 2015)
This paper entitled  Sanmai no Ofuda in Greimas’s perspective. Sanmai no ofuda is the title of Japan’s folktale has similarities with localfolktales from several regions in Indonesia. In this paper, the writer tried to explain the narrative structure of Sanmai no Ofuda in Greimas’s perspective.Its mean to reveal the narrative structure of this folktale,the writer used structural naratology approaches with Algirdas Julien Greimas’s theory. The writer tried to understand about the intrinsic elements  in Sanmai no Ofuda by examining the actans schemes and functional structure. The findings show that the narrative structure can explain  the intrinsic elements more specificly.